2016
DOI: 10.3748/wjg.v22.i26.6057
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing the hepatic vascular architecture using superb microvascular imaging in patients with hepatitis C virus: A novel technique

Abstract: SMI permitted the detailed delineation of the vascular architecture in chronic liver disease. SMI appears to be a reliable tool for noninvasively detecting significant fibrosis or cirrhosis in HCV patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…Previous reports have compared the utility of transabdominal US for microvascular imaging with that of conventional Doppler imaging for the diagnosis of several diseases [27][28][29][30][31][32]. Another microvascular imaging technique similar to DFI, super microvascular imaging, furnishes significantly more information about vascularity than conventional Doppler imaging, making it more suitable for the differential diagnosis of lesions of the breast, thyroid, liver, kidney, and cervical lymph nodes [27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have compared the utility of transabdominal US for microvascular imaging with that of conventional Doppler imaging for the diagnosis of several diseases [27][28][29][30][31][32]. Another microvascular imaging technique similar to DFI, super microvascular imaging, furnishes significantly more information about vascularity than conventional Doppler imaging, making it more suitable for the differential diagnosis of lesions of the breast, thyroid, liver, kidney, and cervical lymph nodes [27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…However, performing transabdominal US to assess microvessels is difficult if the patient is obese (due to the depth of subcutaneous fat). The increased distance between the deeper organs and the probe also has a negative effect on the clarity of the microvascular images [32]. Therefore, to date, no studies into the utility of transabdominal US for microvascular imaging of pancreatobiliary lesions have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…At present, some new ultrasonic technologies have been applied in diagnosis of liver diseases, including superb microvascular imaging and ultrasound elastography, such as shear wave elastography, FibroScan, and acoustic radiation force impulse imaging. They can be helpful for noninvasive evaluation of fatty liver disease, liver fibrosis, and liver tumors [ 6 , 10 , 13 , 16 ]. In recent years, some other researchers have tried to analyze FL by ultrasound RF signals [ 2 , 9 , 18 , 22 ].These studies have revealed that there is a strong correlation between the pathology changes of FL and characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluating the morphologic characteristics of the vasculature at the edge of the liver is thought to be useful for assessing hepatic fibrosis; thus, some researchers investigated the use of SMI. Kuroda et al analyzed the number of vascular trees detected by SMI and found that SMI could aid the detailed delineation of the vascular architecture in hepatic fibrosis. Koyama et al assessed the vascular scores and bifurcation angle in the vasculature detected by SMI.…”
Section: Superb Microvascular Imaging For Characterization Of Liver Dmentioning
confidence: 99%